Flavonoids from Basil Leave as a Potential Inhibitor of SARS-COV-2 Main Protease: an In Silico Approach - Meilinda setya praceka; Farhan Firmansyah; Hafadhoh Arvyna; Gilang F. Dzikrillah; Wa O.I. Fitriah (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
SARS-COV-2 a virus which caused the global pandemic Coronavirus-2019 (COVID-19) has infected about 659,108,952 among, with 6,684,756 deaths in the world as stated by WHO on December 23 2022. Basil leaves have antiviral potential, especially in groups flavonoids. People who are exposed to the COVID-19 virus are given many drugs that cause many side effects. Therefore, it is advisable to consume drugs from natural ingredients that are low in side effects such as basil leaves. This study aims to predict flavonoid derivative compounds from basil leaves that have the potential as an anti-viral drug for COVID- 19 by in silico, which has high affinity with low side effects. The method used is molecular docking for target analysis, prediction of ADME, and prediction of toxicity. The results of this study, there is a naringenin compound that has the highest potential to become an antiviral for COVID-19 with a ∆Gibbs value of -4.04 kcal/mol and an KI of 1.09 mM. These flavonoid derived compounds comply with Lipinski rules, so that the flavonoid content in basil leaves can help treat COVID-19 as a drug derived from natural ingredients that has antiviral potential with low side effects.